(untitled) (The Pakistan Development Review, 1977)
Urbanization is an integral part of the overall process of economic and social development. There is growing evidence that this is the case for Pakistan also. Pakistan in 1972 was nearly 27 percent urban and today is perhaps 30 percent plus urban. The probable distribution by size of place of this growth is of great importance for economic and social planning yet curiously it has received very little scholarly investigation as yet-[7], is an exception and the present article should be viewed as an extension to Helbock’s work. In searching for some model or theoretical statement in the literature regarding what the future hierarchy of urban place in Pakistan will look like, Helbock is naturally lead to the "Rank-Size Rule" vs. "Primate City" question. After examining the 1961 and 1972 census data on urban places by size of place, he concludes that the "Rank-Size" distribution does not adequately describe the Pakistan urban hierarchy.